Predicting Consumer Purchase Intention Through E-Catalogue: A Theory Of Planned Behavior Approach - Paramitha Agdina Pusparini; Hartoyo; Megawati Simanjuntak (Jurnal Manajemen, 2024)
Through Presidential Instruction No. 2 of 2022, the government supports, allocates and spends 40 per cent of the budget value to accelerate the use of domestic goods and MSMEs in government procurement. The government has provided an e-catalogue as an online shopping application that provides products from various commodities the government needs. However, this was followed by something other than the realisation of e-purchasing on the e-catalogue. The purpose was to identify the elements that impact the desire to buy via e-catalogue. Using the criterion of commitment-making officers (CMOs) in local Indonesian governments who purchased laptop items, this research used simple random selection to get 135 respondents. An examination of the data obtained from the e-questionnaire was carried out using SEM. It was shown that several factors, including self-efficacy, perceived behavioural control, attitude, and subjective norms, directly and significantly influenced the intention to purchase. The perceived web quality, however, could have been better.